Possible New Symptoms of Tobacco Withdrawal II: Anhedonia—A Systematic Review. Issue 1 (23rd August 2018) - Hughes, John R; Klemperer, Elias M; Peasley-Miklus, Catherine
Abstract: Introduction: When animals undergo nicotine deprivation, rewards become less rewarding (ie, anhedonia occurs). We searched for tests of whether anhedonia occurs in abstinent smokers. Methods: The major inclusion criterion was a within-participants comparison of behavioral measures of reward sensitivity or self-reported anhedonia during smoking versus during abstinence among daily smokers. A computerized search of PubMed, PsychInfo, and Cochrane databases and other methods located 13 studies. All but one were laboratory studies. Results: The number of studies and participants were small and the results mixed. In terms of anticipatory anhedonia (ie, wanting a reward), abstinence appeared to decrease willingness to work for immediately available rewards, but did not appear to influence how much adding rewards to a task increased responding. Abstinence also appeared to produce small increases in self-reported anticipatory anhedonia. In terms of consummatory anhedonia (ie, liking a reward), self-report measures found anhedonia decreased pleasure from rewards in some but not all tests. In terms of learning (ie, learning to choose a more frequent reward), abstinence did not reliably decrease allocating responding to high versus low frequency reward options. Conclusions: Although results were mixed, abstinence appears to increase anticipatory anhedonia. It is unclear if abstinence increases consummatory or reward learning-based anhedonia. Further studies of anhedonia in clinical settings are needed (1) to estimate the reliability and clinical significance of anhedonia as a symptom of tobacco withdrawal, (2) to assess if effects represent withdrawal versus offset processes, and (3) to assess if anhedonia interferes with the ability to stop smoking. Implications: Anticipatory anhedonia appears to be a symptom of tobacco withdrawal and should be added to tobacco withdrawal checklists and diagnostic criteria. Further study of consummatory and learning-based anhedonia is warranted.